PROCES PRAWODAWCZY DWÓCH DEKAD - SUKCESY I NIEPOWODZENIA - Wronkowska, Sławomira (Wydział Prawa i Administracji UAM, 2009)
The paper offers a synchronic characteristics of the amendments to Polish legislation made over the last twenty years (1989-2009). It accounts for the changes that have taken place in legislative institutions, the law-making rules and procedures, the regulations determining the content of the law, and the political and social environment of the legislation process. Two theses have been formulated: a) there has been a fundamental change in the legislation model, moving from paternalistic to legalistic, manifested, inter alia, by individual’s rights determining the borders which the legislative power must not go beyond, transparency of the law-making rules, and the existence of institutions overseeing the constitutionality o f laws b) the new procedures are still unsatisfactory and fail to fully guarantee elimination o f the dangers of passing defective laws while the legalisation of new provisions continues to receive inadequate social support. The paper ends with a conclusion that political transformations in Poland coincided with the difficult process o f adjusting Polish law to the requirements of the new Constitution and harmonising its provisions with Community law. Although a huge legislative work has been accomplished, modern law making structures guaranteeing stability and functionality of a legal system are still missing.
THE LEGISLATIVE PROCESS OF THE LAST TWO DECADES - SUCCESSES AND FAILURES